DIGITAL EDUCATION AS A SOCIAL AND POLITICAL SPACE: POWER, JUSTICE, AND TRANSFORMATION - Deni Wahyudi; Nuryati Nuryati; Ahmad Zaenudin; Soleha Soleha; Aisyah Aisyah (El Midad, 2026)
The rapid expansion of digital technologies has transformed education in ways that extend beyond technical innovation, reshaping pedagogical practices, governance structures, and the production of knowledge. However, digital education is still predominantly conceptualised through instrumental and technocratic frameworks that prioritise efficiency and performance while neglecting issues of power, justice, and social transformation. This article aims to reconceptualise digital education as a social and political space by developing a critical–transformational paradigm grounded in contemporary educational theory. Employing a qualitative critical literature review, this study analyses and synthesises scholarly works published between 2020 and 2025 that address digital education, critical pedagogy, platformisation, and digital justice. Through critical reading, thematic coding, and conceptual synthesis, the analysis identifies three dominant constructions of digital education: the instrumental-technological, the pedagogical ecosystem, and the socio-political space. The findings reveal that while instrumental and ecosystem approaches contribute to operational understanding, they remain insufficient to address the structural inequalities and power relations embedded in digital education. The study proposes a critical–transformational paradigm that integrates ontological, epistemological, and axiological dimensions, positioning digital education as a value-laden practice oriented toward justice, agency, and social change. This paradigm contributes to theoretical development in digital education and offers a reflective foundation for policies and practices that prioritise pedagogical autonomy, digital justice, and democratic participation.